2001
DOI: 10.1002/1097-4628(20010328)79:13<2331::aid-app1041>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Studies on new type of phenolic resin (IX) curing reaction of bisphenol A-based benzoxazine with bisoxazoline and the properties of the cured resin. II. Cure reactivity of benzoxazine

Abstract: Bisphenol A‐based benzoxazine that contained oligomers (oligo‐Ba) was prepared from bisphenol A, formaline, and aniline. Curing reaction of oligo‐Ba with bisoxazoline and the properties of the cured resin were investigated. Consequently, the ring‐opening reaction of benzoxazine ring occurred, and then the phenolic hydoroxyl group generated by the ring‐opening reaction of benzoxazine ring reacted with oxazoline ring. It was found that the cure induction time and cure time of the molten mixture from oligo‐Ba and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Bisoxazolines are less common in this context 23 , although they have a longer history in the modification of phenolics 24 , conferring lower heat and smoke release properties. The formation of BA-a nanocomposites based on silica 25 and various silicate clay species 26,27,28,29 has been explored and improvements in thermal and mechanical properties can be realized with comparatively modest loadings.…”
Section: Methodsmentioning
confidence: 99%
“…Bisoxazolines are less common in this context 23 , although they have a longer history in the modification of phenolics 24 , conferring lower heat and smoke release properties. The formation of BA-a nanocomposites based on silica 25 and various silicate clay species 26,27,28,29 has been explored and improvements in thermal and mechanical properties can be realized with comparatively modest loadings.…”
Section: Methodsmentioning
confidence: 99%
“…[21] As such, bisoxazolines can be used as the chain extender or crosslinking agent of the polymer. [22] Kimura et al [23,24] reported that the incorporation of bisoxazoline into bisphenol A-based BZ decreased the melt viscosity of the system, and the oxazoline ring could react with the phenolic hydroxy group generated by the ring opening of BZ. Therefore, in our study, the compatibility and reactivity between octaaminophenyl polyhedral oligomeric silsesquioxane (OAPS) and 2,2 0 -(1,3-phenylene)-bis(4,5-dihydro-oxazoles) (PBO) were confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this benzoxazine based resin does not need strong acids catalysts for curing, and does not produce by‐products during curing reaction 9. We also have already investigated the curing behavior of the bisphenol‐A, terpenediphenol, or poly( p‐ vinylphenol)‐based benzoxazines with epoxy resin or bisoxazoline and the properties of the cured resins 10–14…”
Section: Introductionmentioning
confidence: 99%